2020
DOI: 10.3349/ymj.2020.61.5.406
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Personality Traits, Psychological Factors, and Health-Related Quality of Life to Medication Adherence in Patients with Rheumatoid Arthritis

Abstract: This study sought to investigate the associations between personality traits and medication adherence and to identify predictors of good medication adherence in rheumatoid arthritis (RA) patients. Materials and Methods: A total of 207 RA patients using disease-modifying anti-rheumatic drugs were invited for an interview and questionnaire study. Medication adherence was measured using the Compliance Questionnaire for Rheumatology (CQR). Personality traits were analyzed with the five-factor model of the Korean v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
2
16
0
4
Order By: Relevance
“…The researchers have suggested that social demographic, psychological, and clinical factors all can have an impact on medication adherence. 18,19 A recent systematic review showed that pharmacist-led interventions have a positive effect on patients' medication adherence. 20 From this, we infer that patients' psychological factors associated with the pharmacists may play an important role in patients' medication adherence and that it is possible to improve patients' medication adherence through maintaining or improving the patients' psychological contract with pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers have suggested that social demographic, psychological, and clinical factors all can have an impact on medication adherence. 18,19 A recent systematic review showed that pharmacist-led interventions have a positive effect on patients' medication adherence. 20 From this, we infer that patients' psychological factors associated with the pharmacists may play an important role in patients' medication adherence and that it is possible to improve patients' medication adherence through maintaining or improving the patients' psychological contract with pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…In patients suffering from early psychosis, high agreeableness is associated with poor medication adherence (29). In somatic disorders, studies showed that different personality traits mediate medication adherence, and in particular patients who score higher on conscientiousness are more adherent (30)(31)(32). Conscientiousness is defined as the propensity to follow socially prescribed norms for impulse control, to be goal directed, to plan, and to be able to delay gratification (33).…”
Section: Introductionmentioning
confidence: 99%
“…Demographic characteristics are confounding variables that affect compliance with musculoskeletal treatment [ 22 ]. Thus, we incorporated gender, age, marital status, education, and work status as covariates.…”
Section: Methodsmentioning
confidence: 99%